Antibiotic resistance pattern of bacteria causing urinary tract infection in a private medical college hospital, Dhaka (Bangladesh Journal of Medical Science, 2017)
Background and objective: Urinary tract infection (UTI) is one of the frequently seen infections both in the world and in our country as well. Escherichia coli (E. coli) aremost frequently isolated in complicated or uncomplicated, nosocomial or community acquired urinary tract infections. To guide the empirical therapy, the resistance pattern of E. coli responsible was evaluated throughout the period in this study.Material and Method: Urine samples from outpatient / inpatient department of Ibn Sina Medical College Hospital between 1st January, 2015 and 31st December, 2015 were retrospectively analyzed. Presence of ?105 colony forming units/ml in urine culture was considered as significant for UTI. Isolated bacteria were identified by standard laboratory techniques and antibiotic susceptibility testing was performed by Kirby-Bauer disk diffusion method using Clinical Laboratory Standard Institute (CLSI) criteria.Result: A total of 271(13.4%) uropathogens were isolated. Overall E. coli accounted for 180 (66.42%) of all isolates. Resistance rates of E. coli to antimicrobial agents was demonstrated to be as follows: cefuroxime 82%, nalidaxic acid 74%, azithromycin 56%, cefotaxime52%, ceftazidime50%, cefixime 47%, cotrimoxazole 43%, ceftriaxone 41%, ciprofloxacin38%, amoxicillin- clavulanic acid 31%, cefepime30%, and low resistance which ranges from 9 to 1% included gentamycin 9%, meropenem 3%, imipenem2%, nitrofurantoin2% and amikacin 1%.Conclusion: As resistance rates show regional differences, it is necessary to regularly monitor regional resistance pattern to determine the appropriate empiric antibiotic treatment. The national antibiotic usage policies must be reorganized according to data obtained from these studies.Bangladesh Journal of Medical Science Vol.16(1) 2017 p.42-47